Antibacterial Activity Test of the Combination of Bay Leaf (Syzygium polyanthum) Extract and Nanochitosan Against Escherichia coli and Bacillus subtilis - Dewi Mustikaningtyas; Astrid Farmayati; Siti Harnina Bintari; Pramesti Dewi (Universitas Negeri Semarang, 2025)
Indonesia is one of the world’s most biodiverse countries, including in medicinal plants that contain active compounds with potential as sources of modern medicine, particularly for treating bacterial infections. The use of herbal plants as antibacterial agents offers an alternative to overcome antibiotic resistance and the side effects of synthetic drugs. Bay leaf (Syzygium polyanthum) and nanochitosan are known for their antibacterial properties due to their bioactive compounds. However, studies on their combined effects are still limited. This study aimed to evaluate the antibacterial effectiveness of combinations of bay leaf extract (15%, 25%, and 35%) and nanochitosan (0.5% and 1%) against Escherichia coli and Bacillus subtilis. A Completely Randomized Design (CRD) was applied, using sterile distilled water as a negative control and 0.1% chloramphenicol as a positive control. The antibacterial activity test was performed using the Kirby-Bauer disk diffusion method. Results showed the positive control produced inhibition zones of 25.45 ± 1.27 mm for E. coli and 25.05 ± 0.39 mm for B. subtilis. The most effective combination was K3 (35% bay leaf extract and 0.5% nanochitosan), which produced inhibition zones of 12.65 ± 0.52 mm and 12.91 ± 0.55 mm, respectively. Statistical analysis using the Tukey HSD post hoc test confirmed significant differences among treatments. These findings suggest that the combination of bay leaf extract and nanochitosan holds promise as an alternative antibacterial agent